Master Builders. Subaltern Protagonists in the Reconstruction Process of the Valparaiso Hills in Chile - Rivera-Vergara, Héctor Claudio; Campos-Medina, Luis Alfredo (Sociedad y Economía, 2019)
The article inquires in the way master builders as subaltern protagonists act, perceive and explain the reconstruction process of the Valparaiso hills in Chile. The interest of listening to the master builder in his condition as a secondary subject (using a qualitative character methodology, six interviews focused on the master builders, besides twenty interviews to inhabitants affected by the fire, and a process of ethnographic observation in the area for fourteen months), lies in analyzing the meanings of citizenship, hegemony and areas of resistance in the process of reconstruction. In this sense, the results indicate that the mechanisms of solidarity among those who suffer, appear as a resistance to the political-economic hegemony which is based on an individual conscience, working to obtain the well-being and the common good.